DEVELOPMENT OF WORKSHEET INTEGRATED SCIENTIFIC LITERACY FOR PHYSICS PRACTICUM KIT ON ELASTICITY MATERIALS - Anisa Puspa Utami; Hidayati Hidayati; Asrizal Asrizal; Silvi Yulia Sari (Universitas Negeri Padang, 2023)
Education in the era of the industrial revolution 4.0 is not enough just to read and write and numeracy. One of the 16 life skills that students must have in this industrial revolution era is scientific literacy. The aim of the study was to test the effectiveness of using the developed worksheet integrated with scientific literacy. However, worksheets that support literacy activities in the process of learning are still relatively rare and do not support practicum activities. One of the solutions to the problems expressed is to develop scientific literacy integrated worksheets for the use of physics practicum KIT on the material elasticity of materials. The research type used was research and development (Research and Development) or known as R&D. The object of research is worksheets that are integrated with scientific literacy for the use of physics practicum KIT on material elasticity for class XI high school. Research is limited to the product trial stage with a limited scale. Based on the research conducted, 3 conclusions can be drawn. First, the integrated scientific literacy worksheet for the use of physics practicum KIT on material elasticity is very valid with a validity value of 0.85. Second, the practical value of integrated worksheets with scientific literacy obtained from teachers is 94% in the very practical category. The practicality value by students obtained a value of 92% with a very practical category. Furthermore, the use of scientific literacy integrated worksheets is effective in improving student outcomes of learning.